Port Logistics Function Evaluation Model Based on Entropy Weight TOPSIS Method - Zeyun Chen (Discrete Dynamics in Nature and Society)
Port logistics has developed rapidly, but due to late start, poor foundation, and other reasons, there are still some deficiencies in the development process; for example, some port logistics capacity is weak, and low efficiency has hindered the development of ports. Therefore, this paper puts forward the evaluation model of port logistics function based on entropy weight TOPSIS (Technique for Order of Preference by Similarity to an Ideal Solution) method. Analyze the factors that affect the operation effect of port logistics, extract four key indicators, and construct index evaluation factors. Entropy weight method and TOPSIS method are used to calculate the weight of each factor so as to quantify the indicators, thus determining the scoring standard of each indicator, obtaining the comprehensive scoring standard, and realizing the port logistics function evaluation. The experimental results show that to realize the effective use of port resources and the protection of the port environment, it not only needs to conduct port logistics function evaluation but also take into account the efficiency of port logistics. It is of great significance to study the capacity and efficiency of port logistics for improving the core competitiveness of port enterprises and driving the sustainable economic development of surrounding areas.